Search, Bargaining, and Employer Discrimination - Rosén, Åsa (Journal of Labor Economics, 2003)
This article analyzes Becker’s ([1957] 1971) theory of employer discrimination within a search and wage‐bargaining setting. Discriminatory firms pay workers who are discriminated against less and apply stricter hiring criteria to these workers. The highest profits are realized by firms with a positive discrimination coefficient. Moreover, once ownership and management are separated, both highest profits and highest utility can be realized by firms with a positive discrimination coefficient. Thus, market forces, like entry or takeovers, do not ensure that wage differentials due to employer discrimination disappear.